(untitled) (Research, Society and Development, 2022)
Despite the evolution of restorative dentistry, resin adhesion to the dentin surface still presents some obstacles. Among these obstacles are the metalloproteinase enzymes that hydrolyze unprotected collagen filaments and compromise adhesive restorations. Chlorhexidine (CHX) is an antimicrobial widely discussed nowadays to inhibit or delay the action of these enzymes. Therefore, the objective of this study was to evaluate, through the literature, the mechanism of action of chlorhexidine on metalloproteinase enzymes (MMPs) and its clinical impact on the adhesion of composite resin restorations. This research was carried out in the form of an integrative literature review, having a basic nature. For this purpose, Pubmed and Lilacs databases were used with the descriptors “chlorhexidine”, “metalloproteinase”, “hybrid layer”, “clorexidina”, “metaloproteinases” and “camada híbrida”, performing the random crossover and using the operator boolean AND. In view of what has been evaluated, chlorhexidine can be considered beneficial for its clinical use as it can chelate ions that are fundamental for the constancy and function of MMPs, in addition to altering their dimensional structure. However, there is still a need for further studies to evaluate the mechanisms of action of CHX in addition to extensive and in vivo studies regarding its use.